Impacts of Oil Spill on Geotechnical Properties of Soil - Imtiyaz Akbar, Najar; Raudhah, Ahmadi; Showkat, Ahmad Bhawani; Murtala, Namakka; Nur Hisyam, Ramli (Springer, Singapore, 2025)
The escalation of environmental pollution in the world is attributed to the recent increase in crude oil spills, mainly due to the increase in crude oil production and the activities of individuals involved in crude oil theft. In oil and gas, the likelihood of soil pollution from petroleum products soars as oil exploration, production, and transportation of substantial oil volumes via pipelines across vast distances continue to dilate. Recent findings divulge a plethora of instances of oil spills occurring in various locations, attributed to damage within the infrastructure of the oil industry. These spills have resulted in soil contamination, giving rise to significant environmental risks and degradation of both the soil and its engineering characteristics. Herein we explore the changes in geotechnical properties of soil resulting from oil contamination. Beyond understanding the detrimental effects, the chapter explores numerous treatment methodologies, both established and emerging, offering a roadmap for restoring the geotechnical integrity of oil-contaminated soil. The advantages of employing geotechnical approaches, including sustainability, cost-effectiveness, and long-term efficacy, are highlighted, looking ahead, we identify key areas emphasizing the need for long-term monitoring, exploration of emerging contaminants and technologies like nanotechnology, for the development of scalable and cost-effective solutions.